Hierarchical to Gender Egalitarianism: Women Empowerment and Emancipation through Micro Finance in Rural Nepal - Upadhyay, Prakash (Journal of Nepalese Business Studies, 2016)
The major objective of this paper is to identify the efficacy of Micro Finance in women empowerment and to explore the ramifications of awareness and socioeconomic alterations owing to Micro Finance program. Both quantitative and qualitative data from primary and secondary sources were used in the study. The instruments of primary data collection were questionnaire, observation, interview and focus group discussion. Pedestal on gender theories examining status and power differences related to gender empowerment, role of caste, ethnicity, culture and, to some extent, class status in shaping individuals and problems, this study deduced that gender empowerment is a transformation of gender relations from hierarchal to egalitarian plan rather than just women’s power position and this has been doable through Micro Finance which has proved to be the financial self sustainable paradigm. Microfinance program has supported to women’s income generating and livelihood activities and helped in poverty reduction owing to which rural women’s life style and way of living is altering. Gender empowerment through Micro Finance incorporates emancipation and empowerment of women without creating a misgiving of emasculation of men. Emancipation of women is procuring economic, social and political rights and equality meant for fostering a balance in gender relations as against the one-sided women empowerment approach. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 48-62